1992
DOI: 10.1176/ajp.149.6.778
|View full text |Cite
|
Sign up to set email alerts
|

A crossover study of focused cognitive therapy for panic disorder

Abstract: Focused cognitive therapy offers a promising nonpharmacological alternative for the treatment of panic disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(4 citation statements)
references
References 15 publications
1
2
0
1
Order By: Relevance
“…In any case, the long-term therapeutic advantage of integrated therapy over pharmacological treatment was quite large, and it was independent from known prognostic factors. Our results, together with those of other studies [10, 12, 13, 46], cast some doubt on the view that long-term drug treatment is the most appropriate therapy for patients with panic disorder.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In any case, the long-term therapeutic advantage of integrated therapy over pharmacological treatment was quite large, and it was independent from known prognostic factors. Our results, together with those of other studies [10, 12, 13, 46], cast some doubt on the view that long-term drug treatment is the most appropriate therapy for patients with panic disorder.…”
Section: Discussionsupporting
confidence: 55%
“…However, studies examining the long-term outcome of treatments are not abundant. Psychotherapy has been found to have lasting effects, with the majority of patients maintaining treatment gains for 1 year or more [10, 11, 12, 13]. There is also evidence that long-term drug treatment of panic disorder is effective [14].…”
Section: Introductionmentioning
confidence: 99%
“…In CT, exposures serve to elicit cognitive change through the modification of erroneous assumptions. Randomized controlled trials have shown the efficacy of CT over supportive therapy (Beck et al, 1992), applied relaxation, and imipramine (Clark et al, 1994). Moreover, Clark et al (1999) found that a brief five sessions of CT was as efficacious for PD as receiving the full course of CT.…”
Section: Treatment and Efficacymentioning
confidence: 99%
“…Beweise und Demonstrationen der generellen Wirksamkeit von Psychotherapie (Glass, 1976;1978;Glass, McGaw & Smith, 1991) Vom narrativen Review unterscheidet sich die Metaanalyse (Glass, 1976;1978;Glass, McGaw & Smith, 1981) (Beck, Sokol, Clark, Berchick & Wright, 199;Borkovec & Costello, 199;Barrowclough et al 001;Markowitz et al 1998). Bei weiteren Studien präsentierte sich das SC verglichen mit der CBT nach temporären Schwächen in den Post-Treatment-Werten als überlegen in den Follow-up-Effekten (Kolko, Brent, Baugher, Bridge & Birmaher, 000;Tarrier, et al 1998;Tarrier et al 000) Die Praktiken und die methodische Vorgangsweise, mit der "supportive counseling" beschrieben wird, weisen eher darauf hin, dass eine Addition und Kombination von verschiedenen Skills und Techniken vorgenommen werden, die sich mit den "core conditions" bzw.…”
unclassified